O consumidor de moda no Rio Grande do Sul: características e percepções (ModaPalavra e-periódico, 2009)
The aim of this paper is to analyze the fashion in the southernmost Brazilian state Rio Grande do Sul in order to verify the behavior of the consumer in this State and if it differs from the behavior of the consumer in the State of São Paulo. It presents, firstly, a report of the gaucho fashion and a brief analysis of the identity of the people that live in this State. Secondly, it presents a panorama of the Brazilian fashion market, focusing on the consumer and on the textile and fashion making sectors all over the country and specifically in Rio Grande do Sul. Finally, relying on a qualitative field research applied to fashion professionals inserted in the gaucho market, the paper tries to capture the singularity of the fashion consumers of Rio Grande do Sul.
Keywords: gaucho fashion; identity; consumer